Rancang Bangun Automatic Weighing System untuk Aplikasi Mesin Mixer - Fismatika, Akhmad Tito; Sandi, Aris; Setyawan, Martin Andre; As'ari, Farhan; Kurniawan, Wahyu (Lembaga Yasin AlSys, 2025)
The greater human need for livestock continues to increase along with increasing population growth. Therefore, optimization is needed in the livestock processing process, while some livestock equipment today is still classified as conventional, which still uses human power and is manual in nature, for example the animal feeding system. With the development of technology that can be applied to the shutter, it is necessary to optimize animal feeding systems such as automatic weighing systems. The automatic weighing system is one of the innovations that supports the performance of a mixing tool (mixer) which is designed to mix unused plantation industry waste such as sugar cane shoots, palm fronds, bagasse, palm oil meal, etc. in the animal feeding system. This research begins with a search for related literature, followed by making a tool design which then based on the design that has been made this tool can be realized accompanied by testing whether this tool is in accordance with the desired specifications. The progress of this research is in the stage of making schematic wiring diagrams for making printed circuit board (PCB) lines. Next, all electronic components used on the bread board are transferred to the PCB and then PCB prototyping testing is carried out to analyze wiring path errors on the PCB. The next stage is to apply a load to the load cell to ensure the correctness of the program/coding that has been created and the accuracy of the reading results for the given load. Based on the tests that have been carried out, the measurement results are still within tolerance so that this Automatic Weighing System tool is suitable for use. As a final stage, a mechanical system will be created to apply an automatic weighing system that uses this load cell on each leg of the mixer machine.